Beyond Bilingualism: Gustaf Wingren and the Public Voice of Diaconia - Fagermoen, Tron (Diaconia, 2020)
The political and public dimensions of diaconia are increasingly being acknowledged. This in turn necessitates a discussion of the language agents of diaconia should use when expressing their views in the public sphere. Should they articulate their concerns in a so-called secular language, accessible also to those who do not share the Christian faith? Or should they use the distinctive language of their specific religious tradition? The article proposes that the political ethics of the Swedish theologian Gustaf Wingren (1910-2000) provides a rewarding starting point for addressing this issue. With his dialectical approach to the distinction between law and Gospel, universality and particularity, Wingren contributes to an understanding of the public voice of diaconia, which not only moves beyond the alternatives of distinctiveness and accessibility but which also challenges the concept of bilingualism, a concept that has become central to contemporary public theology. Thus, it is argued, Wingren paves the way for conceptualizing the public voice of diaconia and provide it with the rhetorical flexibility, dialogical reciprocity, and polyphonic diversity needed to constructively engage a postsecular public sphere characterized by religious complexity.